Challenges and Opportunities in the Dynamics of the Multi-Party System in Indonesia - Hajar, Siti (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The multi-party system in Indonesia has experienced significant dynamics since the Reformation era, marking an important change in the journey of democracy in this country. Political freedom obtained after the reformation paved the way for the birth of many new political parties that participated in the general election, so this is the reason for the creation of a complex multi-party system and provides various challenges and opportunities for the consolidation of democracy in Indonesia. This study aims to determine and describe the challenges and opportunities of the multi-party system in strengthening democracy in the Reformation era. The method used in this study is qualitative. The results of the study show that the multi-party system in Indonesia in the effectiveness of political party management is still dominated by elite figures and families so that parties function more as individual political vehicles than institutions that represent the interests of the wider community, and this is the main challenge for the multi-party system in Indonesia. Then, the most highlighted opportunity is the increase in political representation for democracy in Indonesia. The multi-party system allows various interest groups, including minorities, to establish parties and compete in general elections. This opens up space for various political aspirations that may not be represented in a two-party system or a one-party dominance system. This political pluralism should be able to create public policies that are more inclusive and represent the interests of various levels of society. In addition, a multi-party system can also encourage the emergence of new, fresher and more innovative parties, as well as provide alternatives for voters who may be dissatisfied with the existing major parties.